Jápa, Jánù, Jápadà: Dynamics of Migration Discourse in Adekunle Gold’s Music- “Ire” - Adekola, Olaolu Emmanuel Adekola (African Journal of Stability and Development (AJSD), 2025)
Migration is a common phenomenon in human experience, which has manifested in a new concept called Jápa in Nigeria. Jápa, as a concept, has received scholarly attention in academic discourses in recent years, but earlier studies from sociology, health, education, economics, language, religious and cultural studies have focused more on its causes and effects on Nigerian economic development; however, scanty attention has been paid to its dynamics among Nigerians, especially from a musicology perspective. This study, therefore, examined Jápa, Jánù, and Jápadà as migration dynamics using Adekunle Gold’s music- “Ire” to discuss the resultant effect of emigrants’ aspiration, failed quest, and reasons for the emigrants to retreat in their attempt at forceful ambitions. The study adopted a qualitative method to gather data using Adekunle Gold’s music track “Ire” through purposive sampling technique. The data (music content) were content analysed. The phenomenon of Jápa has taken different dimensions in which the aspiration of an emigrant may result in loss of identity, loss of worth, loss of freedom, loss of life, and deportation after a huge investment has been made to pursue the abortive ambition. Adekunle Gold’s music track, “Ire”, is therefore an encouragement and motivation to the emigrants to look inward and retreat if the aspiration is not achieved to avoid colossal loss in the end. It is recommended that artistes should do more in enlightening the citizenry on the need to “water one’s ground” and make it greener instead of seeking a greener pasture somewhere else, where there are uncertainty and bait for voluntary slavery.